Intra-Operative Neural Response Telemetry and Acoustic Reflex Assessment using an Advance-In-Stylet Technique and Modiolus-Hugging : A prospective cohort study - Abdulrahman Hagr (Sultan Qaboos University Medical Journal, 2011)
Objectives: The development of cochlear implant (CI) electrode arrays has focused on the use of a minimally invasive technique involving a modiolus-hugging placement of the electrode. The aim of this study was to evaluate the “advance-in-stylet” (AIS) technique compared to the advance-off-stylet (AOS) technique recommended for the current cochlear Nucleus® device. In the AIS technique, the stylet is not removed. We evaluated the electrical auditory thresholds measured when the stylet was removed (modiolus-hugging) compared to measurements taken with the stylet in place (lateral wall cochlea electrode placement). Methods: In this prospective cohort study, 30 consecutive patients received unilateral Nucleus Freedom® CIs using AIS insertion. Measurement of the acoustic reflex (AR) and neural response telemetry (NRT) were performed with the stylet in place (lateral wall placement of the electrodes) and then removed (perimodiolar placement), and the results compared. The responses were measured in the basal, middle and apical turns in both groups—with and without stylet. Results: The AIS surgery was completed without complication in 30 patients (16 males and 14 females, age range 3-54 years [mean 11]). Based on neural response telemetry, only apical electrodes showed statistically significant differences in thresholds, but the AR was not significantly different before or after stylet removal in any of the electrode groups tested. Conclusions: The effects of modiolus-hugging do not seem to result in a large difference in electrical stimulation thresholds so, in difficult cases, the stylet may be left in place without significantly changing the thresholds, except perhaps at the apical turn.